3D graphene/ZnO composite with enhanced photocatalytic activity. (15th January 2016) - Cai, Ran; Wu, Jia-gen; Sun, Li; Liu, Yan-jun; Fang, Ting; Zhu, Shan; Li, Shao-yang; Wang, Yue; Guo, Li-feng; Zhao, Cui-e; Wei, Ang
Abstract: In this study, a three-dimensional (3D) graphene/ZnO nanorod (G/ZnO) composite was synthesized by chemical vapor deposition (CVD) and simple hydrothermal method. Integration of 3D graphene and ZnO nanorods leads to a high performance in photocatalytic degradation toward methyl orange (MO). The results indicate that the 3D G/ZnO composite achieves a higher degradation efficiency under UV light than pure ZnO nanorods. The enhancement of photocatalytic activity can be attributed to effective separation of photo-generated electrons and holes at the interface of graphene and ZnO. Graphical abstract: A novel three-dimensional graphene/ZnO (G/ZnO) composite was successfully prepared by chemical vapor deposition (CVD) and simple hydrothermal method, and used as the photocatalysts for MO degradation. The results showed that the photocatalytic performance of the G/ZnO was enhanced compared with that of pure ZnO, which can be attributed to the large surface area and reduced charge carrier recombination at the interface of the G/ZnO composite. Highlight: The 3D graphene/ZnO composite was synthesized by chemical vapor deposition and hydrothermal treatment. The G/ZnO composite exhibits a higher degradation efficiency toward methyl orange (MO) than that of the pure ZnO nanorods. The improved photocatalytic activity can be attributed to effective separation of photo-generated electrons and holes.